Employee Performance and Sustainability Trends Throughout 25 Years: A Bibliometric Analysis - Putri, Rizky Atika Salsabila Ivabianca; Salsabila, Winnita Sofna; Khairunnisa, Shafira (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2025)
This article presents a comprehensive bibliometric analysis of employee performance and sustainability research globally, covering a 25 year span from 2001 to June 2025. The study’s primary purpose is to identify emerging trends, research gap between employee performance and sustainability practices in business, including unexplored key research themes and future directions to provide valuable insights for academics, policymakers, and practitioners seeking to understand and advance employee-related sustainability practices. We employed a bibliometric approach, collecting 573 articles from the Scopus database. Analysis of the data was carefully done using Microsoft Excel, OpenRefine, VOSViewer, RStudio, and Biblioshiny to allow for extensive citation, content, and network analysis. As a result, we identify four research clusters which include First, environmental sustainability and green hrm practices. Second, employee performance and organizational behavior. Third, strategic sustainability and innovation, and Four general linking themes. Furthermore, we found several research gaps for future exploration, such as exploring innovation as a mechanism linking sustainability efforts and employee performance. This offers clear directions for early-career scholars in the field of employee performance and sustainability.